تقييم الأداء المالي وتحليل المردودية في المؤسسات الخدماتية دراسة حالة مؤسسة اتصالات الجزائر فرع سوق أهراس - - خلال الفترة 2017-2019- - محمد الأمين معواج; إيمان بروك (My University, 2022)
اThis study aims to evaluate the financial performance of the service institution and analyze its profitability using several indicators and financial ratios, and to highlight the role that these indicators play in order to identify and strengthen the strengths and weaknesses and find appropriate solutions for them, The application of this study to the practical reality Algeria Telecom has a Souk Ahras unit for the period from 2017 to 2019. It was found through this study that the institution did not achieve acceptable performance in most of its activities, despite having an acceptable amount of liquidity, but it did not achieve growth in terms of net profits, and it did not achieve significant rates in profitability indicators. The results of the study also showed that the lack of optimal control over expenses and the optimal use of the institution's resources had a negative impact on its profitability, as it achieved very poor profitability during the years of study. ............................................................... تهدف هذه الدراسة إلى تقييم الأداء المالي للمؤسسة الخدماتية وتحليل مردوديتها باستعمال عدة مؤشرات ونسب مالية، وابراز الدور الذي تلعبه هذه المؤشرات للوقوف على نقاط القوة وتعزيز ونقاط الضعف وايجاد حلول مناسبة لها، واسقاط هذه الدراسة على الواقع العملي لمؤسسة اتصالات الجزائر وحدة سوق أىراس للفترة من 2017 الى 2019. وقد تم التوصل من خلال هذه الدراسة أن المؤسسة حيث لم تحقق أداء مقبولا في معظم أنشطتها رغم امتلاكها قدرا مقبولا من السيولة لكنها لم تحقق نموا على مستوى الأرباح الصافية وكذلك لم تحقق معدلات كبيرة في مؤشرات الربحية. كما أظهرت نتائج الدراسة أن عدم التحكم الأمثل في المصاريف والاستغلال الامثل لموارد المؤسسة أثرا بشكل سلبي على مردوديتها حيث أنها حققت مردودية ضعيفة جدا خلال سنوات الدراسة.